Irrigation management of common bean cultivars with contrasting growth habits - Coelho, Anderson Prates [UNESP]; de Faria, Rogério Teixeira [UNESP]; Lemos, Leandro Borges [UNESP]; Dos Reis, Maria Albertina Monteiro [UNESP]; Filla, Vinicius Augusto [UNESP]; Bertino, Antonio Michael Pereira [UNESP] (FapUNIFESP (SciELO), 2022)
A study was undertaken comparing the water requirements of two common bean (Phaseolus vulgaris L.) cultivars to generate specific recommendations aimed at optimizing water use. To accomplish this work, the agronomic performance, responsiveness to water and water productivity of these two common bean cultivars of determinate and indeterminate growth habits were identified. The 2-year experiment was carried out during the winter growing season in the southeast of Brazil. Cultivars IAC Imperador, with an early season of determinate growth habit, and IPR Campos Gerais, having a mid-season of indeterminate growth habit, were subjected to five irrigation levels (54, 70, 77, 100, and 132 % of the crop evapotranspiration). Water deficit affected agronomic performance, reducing plant height (by up to 29 %), leaf area index (by up to 40 %), soil cover fraction (by up to 28 %), and grain yield (GY-by up to 31 %), in both cultivars. In contrast, excess water was more detrimental to cultivar IAC Imperador. Cultivar IPR Campos Gerais produced 18 % more than GY, showing superior water productivity and response to irrigation depth than IAC Imperador. Out of all the variables evaluated, the soil cover fraction correlated the most with grain yield in both common bean cultivars during the 2-year study. In other words, cover fraction evaluation in common bean allows for estimating crop production potential, which helps producers and technicians in their decision making regarding management practices. Thus, a cultivar directly affects water use in common bean production, thereby suggesting the need for a or water conservation strategy and sustainability of irrigated common bean production.
Keywords: cover fraction; grain yield; leaf area index; Phaseolus vulgaris L; water deficit